Removal of a Dental Implant from the Maxillary Sinus by Caldwell–Luc Surgery: A Case - Bozoğlan, Alihan; Dündar, Serkan; Öztürk, Besime Büşra (My University, 2019)
Displacement of an implant into the maxillary sinus is a rare complication in dental implant clinicalpractice. This complication mainly arises due to an inadequate bone height and peri-implantinfection. The presence of a foreign object, such as an implant, in the maxillary sinus causessinusitis via impaired mucociliary flow and foreign body reactions. Therefore, foreign object inmaxillary sinus must be removed. Caldwell–Luc surgery may be performed to remove foreignbodies and lesions from the maxillary sinus. Herein, we describe the case of a patient whose dentalimplant slipped into the right maxillary sinus during the insertion of the healing cap due toperiimplant infection and removal of the implant via an intraoral Caldwell–Luc surgical approach.The intraoral Caldwell–Luc surgery technique proved to be a safe, reliable method for the removalof a foreign object from the maxillary sinus.
Keywords: Genel ve Dahili Tıp; Diş Hekimliği; Cerrahi